2008
DOI: 10.1007/s00534-008-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

A simple, noninvasively determined index predicting hepatic failure following liver resection for hepatocellular carcinoma

Abstract: Background A novel index, the serum aspartate aminotransferase activity/platelet count ratio index (APRI), has been identified as a biochemical surrogate for histological fibrogenesis and fibrosis in cirrhosis. We evaluated the ability of preoperative APRI to predict hepatic failure following liver resection for hepatocellular carcinoma. Methods Potential preoperative risk factors for postoperative hepatic failure (hepatic coma with hyperbilirubinemia, four patients; intractable pleural effusion or ascites, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…[8,22] Ichikawa et al [23] reported that preoperative APRI independently predicted hepatic failure following liver resection for HCC, and patients with an APRI of 10 or more have a high risk of postoperative hepatic failure. In the present study, we identified APRI was an independent risk factor for overall postoperative complications by univariate and multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…[8,22] Ichikawa et al [23] reported that preoperative APRI independently predicted hepatic failure following liver resection for HCC, and patients with an APRI of 10 or more have a high risk of postoperative hepatic failure. In the present study, we identified APRI was an independent risk factor for overall postoperative complications by univariate and multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The FIB4 index was calculated using the following formula: (age [years] × AST [U/L])/(Platelet Count [10 9 /L]) × √ALT [U/L] [16]. According to previous reports, we set the cutoff values of the ALBI score, APRI, and FIB4 index at –2.60, 1.00, and 2.67, respectively [7, 14, 17]. …”
Section: Methodsmentioning
confidence: 99%
“…Similar to the CPT score, the MELD score works well for patients with marginal liver function, but it fails to differentiate the surgical risk in those patients in which HCC is more suitable for resection. While the APRI score is promising, there are few reports of discussing APRI score [4]. Similar to the CPT and MELD scores, the APRI score seems adequate for patients with advanced liver disease, i.e.…”
Section: Liver Resectionmentioning
confidence: 99%